Design and production of environmentally degradable quaternary ammonium salts. Issue 17 (10th August 2021) - Zhang, Xiaolong; Kong, Hongtao; Zhang, Xuepeng; Jia, Hengmin; Ma, Xiuxia; Miao, Hui; Mu, Yan; Zhang, Guoqing
Abstract : Our QACs, being cost-effective and naturally degradable, have the potential to replace their currently-used more-stable counterparts as a universal active ingredient for disinfectant products. Abstract : Quaternary ammonium compounds (QACs) are a class of cationic surfactants routinely used for the disinfection of industries, institutions and households, and have seen a sharp increase in use during the COVID-19 pandemic. However, current commercial QACs consist of only stable chemical bonds such as C–N, C–C, and C–H, which makes their natural degradation rather difficult. Recent studies suggest that emerging negative environmental impacts, such as systemic antibiotics resistance and toxicity to living organisms, are directly associated with prolonged exposure to QACs. Here we report a new class of QAC which contains relatively volatile chemical functional groups such as ester and thioether bonds. Degradation kinetics in aqueous solutions suggests that the stability of these QACs depends not only on their intrinsic hydrophobicity but also on external environmental factors such as pH, temperature and ion presence. The microbicidal effects of QACs containing carbon chains with various lengths were also tested, one of which, named "Ephemora", is highly active against a broad spectrum of microbes including fungi, bacteria and viruses, for instance, methicillin-resistant Staphylococcus aureus (MRSA). The easy synthesis and purification of Ephemora starting from inexpensive commercially available reagents, together with its excellent antimicrobial activity and ability to degrade in natural waters over time, make its large-scale commercial production possible.